Pola Resistensi Kuman Mycobacterium Tuberculosis terhadap Obat Anti Tuberkulosis Lini Pertama - Natalia Yobeanto; Theresia Lolita Setiawan (Syntax Corporation Indonesia, 2022)
Pulmonary Tuberculosis (pulmonary TB) is a chronic infectious disease caused by Mycobacterium tuberculosis which is still a major public health problem in the world, including Indonesia. One of the biggest challenges in current TB control program is Multi Drug Resistance TB (MDR-TB). Multi Drug Resistant Tuberculosis (MDR-TB) is a complicating factor in TB disease control because it provides a high burden of morbidity and mortality (50–60% in five years). This literature review aims to increase knowledge about the pattern of first-line antituberculosis drug resistance so that it can early diagnose any suspected drug-resistant TB, prevent drug-resistant TB, and as a reference for conducting further research. This literature review was conducted through PubMed and Google Scholar searches with English and Indonesian articles, then all articles that met the inclusion criteria were analyzed. Based on literature studies from several studies, the most common pattern of resistance is rifampin or isoniazid-resistant TB, followed by resistance to rifampin and isoniazid. Most of the patients were relapse cases. To establish a diagnosis of TB drug resistance begin with identifying risk factors and accelerating laboratory diagnosis. Early detection and initiation of MDR-TB therapy is the to the successful treatment.